Faster progression to multiple sclerosis disability is linked to neuronal pathways associated with neurodegeneration: An ethnicity study. - Gil Harari; Michael Gurevich; Mark Dolev; Rina Zilkha Falb; Anat Achiron (PLoS ONE, 2023)
Although the causes of multiple sclerosis are largely unknown, genetic and environmental components play an important role. Geographic distribution, varying with latitude, reflects both genetic and environmental influences. We conducted a retrospective exploratory observational study to characterize the disability progression of 2396 Jewish patients with relapsing-remitting multiple sclerosis, followed at the Sheba Multiple Sclerosis Center, Tel-Aviv, Israel; 188 patients who originated in Iraq and 2207 patients who originated in northern Europe. Peripheral blood microarray gene expression analysis was performed in a subgroup of patients to identify molecular pathways associated with faster disability progression. During a follow-up period of 18.8 and 19.8 years, respectively, 51.6% of patients with an Iraqi origin progressed to moderate disability defined as expanded disability status scale (EDSS) score of 3.0 to 5.5, compared to 44.2% of patients with a northern European origin (odds ratio 1.347, 95% CI 1.0-1.815, p = 0.049). An Iraqi origin was associated with increased risk of progression to moderate disability adjusted for sex, disease duration, age at onset, and treatment with immunomodulatory drugs (hazard ratio 1.323; 95% CI, 1.049-1.668, p = 0.02), but not to severe disability defined as EDSS score > = 6.0 (i.e., walking aids are required for a distance of 100 meters, (hazard ratio 1.311; 95% CI, 0.918-1.874, p = 0.136). Gene expression analysis disclosed 98 differentially expressed genes (79 over-expressed and 19 under-expressed) between relapsing-remitting multiple sclerosis patients of Iraqi origin (N = 17) and northern European (N = 34) origin. Interestingly, this gene expression was enriched with genes related to neuronal pathways associated with morphology of axons, branching of neurites, proliferation of neocortical neurons, and formation of myelin sheath, suggesting an augmented process of neurodegeneration in relapsing-remitting multiple sclerosis patients with an Iraqi origin. The study results suggest that relapsing-remitting multiple sclerosis patients with an Iraqi origin progress faster to disability possibly due to an enhanced process of neurodegeneration.